2016
DOI: 10.1007/s10584-016-1767-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of environmental change and migration decisions

Abstract: While climate change is projected to increase displacement of people, knowledge on this issue remains limited and fragmented. In his paper we focus on the micro-level and study the effects of individual perceptions of different types of environmental events (i.e., sudden/short-term vs. slow-onset/long-term) on migration decisions. Our results based on newly collected micro-level survey data from Vietnam shows that while slow-onset environmental events, such as droughs, significantly decrease the likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 40 publications
(37 reference statements)
2
26
0
7
Order By: Relevance
“…Several researchers relied on a combination of interviews and regression analysis (Greyet al, 2014; Koubi et al., 2016; Snodgrass et al., 2016). Gray et al.…”
Section: Methodological Approaches To Environmental Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers relied on a combination of interviews and regression analysis (Greyet al, 2014; Koubi et al., 2016; Snodgrass et al., 2016). Gray et al.…”
Section: Methodological Approaches To Environmental Displacementmentioning
confidence: 99%
“…Koubi et al. (2016) looked at both slow and sudden‐onset environmental issues and short and long‐term environmental issues in three communities in Vietnam to understand perceptions of environmental change and displacement possibilities related to these temporal scales. They found that social and economic factors influence a person's decision to move more than short term events, such as a flood.…”
Section: Methodological Approaches To Environmental Displacementmentioning
confidence: 99%
“…Algumas pesquisas assinalam uma queda de cerca de 80% na produção agrícola do semiárido em períodos de secas (Khan et al, 2005), intensificando os processos migratórios (Barbieri, 2011) e reconfigurando as situações de vulnerabilidade no território (Adger et al, 2015). Por outro lado, não há consenso na literatura, tanto na discussão se a migração seria uma alternativa de adaptação ou se ela contribuiria para reiterar cenários de vulnerabilidade (Barbieri, 2011) quanto na intensificação desses movimentos populacionais motivados por mudanças ambientais (Adger et al, 2015;Koubi, Stoll, Spilker, 2016). Além das perdas na produção e na receita agrícola, o efeito das estiagens sobre o emprego (Khan et al, 2005) podem contribuir para realçar o modo de Isac Alves Correia, Ricardo Ojima, Alisson Flávio Barbieri vida das cidades que se estende para além das metrópoles (Monte-Mór, 2006;Baeninger, 2012) integrando as atividades agrícolas e não-agrícolas (Vanwey, Guedes, D'antona, 2012) e a busca por serviços públicos .…”
Section: Migração Seca E Vulnerabilidade No Semiárido Brasileiro E Nunclassified
“…68 Moreover, recent research contrasts individual perceptions of environmental events with actual climatic events and finds that migrants and non-migrants indeed perceive climate change in different ways. In particular, while nonmigrants are slightly better in judging the actual extremeness of sudden, short-term events, migrants are slightly more accurate in assessing the actual extremeness of gradual, long-term events (Koubi, Stoll, and Spilker 2016). The appendix provides the survey questions, and also outlines what specifically refers to an environmental event and how this is measured.…”
mentioning
confidence: 99%
“…While nonmigrants are slightly better in judging the actual extremeness of sudden, short-term events, migrants are slightly more accurate in assessing the actual extremeness of gradual, long-term events. Koubi, Stoll, and Spilker 2016. The appendix provides the survey questions, and also outlines what specifically refers to an environmental event and how this is measured.…”
mentioning
confidence: 99%